Government finance statistics - International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2015)
The GFS presentation is similar to that of business accounting where the profit and loss accounts and the balance sheet are presented together, in an integrated manner. The emphasis is on the economic substance over the legal form of the event. Hence GFS differ noticeably from the budget or public accounting presentations that are nationally specific as far as scope of units and recording of transactions are concerned
"Database and browser." Computer discs Available also in print format: Government finance statistics yearbook Online version is also available
Keywords: Budgets and budgeting; FINANCE; FINANCIAL STATISTICS; DATA BASES; PERIODICALS